HUBUNGAN PELAKSANAAN KESELAMATAN PASIEN (PATIENT SAFETY) PADA RUANGAN ICU (INTENSIFE CARE UNIT) DI RSUD ARIFIN ACHMAD PEKANBARU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Patient safety is freedom from accidental injury or to avoid injury to the patient due to medical care and patient safety medication errors (patient safety) hospital is a system where hospitals make patient care safer.The purpose of this study was to determine the relationship of the implementation of patient safety (patient safety) in a general hospital ICU room area arifin achmad Pekanbaru 2015. This research method is a type of research is quantitative analytical cross sectional study design in which the variables studied, observed, and collected at the same time number of samples in this study were 68 respondents. Sampling technique in this research is to use total sampling, and for data collection is done by using a questionnaire. The analysis of univariate and bivariate data using Chi Square test.The results showed an association between clinical aspects (P value 0.016 <0.05) of efficiency and effectiveness (P value 0.023 <0.05). While that is not related aspects of keselelamtan patients P value (0.386> 0.05). Advised on leadership Hospital arifin area achmad Pekanbaru to always perform oversight and improvements in the performance of existing health workers in public hospitals arifin area achmad especially nurses in order to improve health care safety, and occupational health in the process of patient treatment and thus contribute services maximum.